Pengaruh Model Problem Based Learning (Pbl) Berbantuan Phet Simulation untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Qothrunnada, Qothrunnada; Ayub, Syahrial; Gunada, I Wayan; Kosim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to examine whether the Problem-Based Learning (PBL) model assisted by PhET Simulation has an effect on students’ critical thinking skills. The type of research used was a quasi-experimental design with a non-equivalent control group design. The population in this study consisted of all grade XI science classes at SMA Negeri 1 Gerung. The sample was selected using saturated sampling, with class XI F (36 students) as the experimental group and class XI G (34 students) as the control group. The experimental group received treatment using the Problem-Based Learning (PBL) model assisted by PhET Simulation, while the control group was taught using conventional learning methods. The test instrument consisted of five essay-type questions. The hypothesis was tested using the Independent Samples t-test at a 5% significance level, which produced a significance value of 0.001 for students’ critical thinking skills. Since this value is smaller than the 5% significance level (0.050), H0 was rejected and Ha was accepted. These results indicate that the PBL model assisted by PhET Simulation has a significant effect on students’ physics problem-solving skills, further supported by the higher N-Gain score of the experimental class compared to the control class.